Self-evaluation in European schools : a story of change - MacBeath, John, 1940- (Routledge, 2000)
In a political and economic climate in which school performance is made public, performance tables and inspectors' reports can only tell a partial story. This is a unique book. It tells the story of one school seen through the eyes of a pupil, a parent, a teacher, a headteacher and a critical friend. The story is a compelling journey through the process of school improvement; theories of school effectiveness and school improvement are progressively clarified. This book is based on a well-known and well-documented research project that represents eighteen European countries, which clearly.